Peran Masyarakat Berbasis Agama dalam Mewujudkan Anggaran Daerah âPro Poorâ Sebagai Upaya Pengentasan Kemiskinan Di Kabupaten Bintan - Alfiandri, Alfiandri; Wahyuni, Sri (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2014)
The local annual budget (APBD) is one of the instruments of government policy to finance developmentprograms, services and empowerment in the area. Budgets are formulated by local governments andlegislators to advance aspiration developed in the society. Nevertheless, the budget policy area alwaysbiased interests, both political interests and the interests of local control of resources. Therefore, thecommunity can play a role in determining the area of pro-poor budget for poverty alleviation efforts inthe area. Faith-based societies, including in the civil society organizations that play a role in achievingpro-poor local budgets. This study is intended to look at the role, which the researchers analyzed the roleof faith-based communities in achieving pro-poor local budgets in an effort to alleviate poverty in Bintanregency. To achieve these objectives, this study used a qualitative approach. This approach is veryrelevant to see and map the role of faith-based communities in achieving pro-poor local budgets. Thisstudy concluded that the role of faith-based communities have not been effective in achieving pro-poorlocal budgets. This is due to a lack of faith-based public awareness of the role and responsibilities, lack ofinstitutional and managerial faith-based community organization and lack of socialization of thegovernment.